PERBANDINGAN INSIDENSI HIPOTENSI SAAT INDUKSI INTRAVENA PROPOFOL 2 mg/KG BB PADA POSISI SUPINE DENGAN PERLAKUAN DAN TANPA PERLAKUAN ELEVASI TUNGKAI - INDRA, BENI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Background : The induction of general anaesthesia with propofol may induce of considerable degree of hypotension. The hypotensive effects of propofol has been atributed to decrease in systemic vascular resistance caused by combination of venous and arterial vasodilatation. It will produce a shifting of blood to venous reservoir, especially capacitance venule of legs. Passive leg raising is simple maneuver that provide hemodynamic stability by increases cardiac preload and recruits blood contained in the venous reservoir and distributes it to the cardiac cavities. Methods : This is Open Randomized Control Trial include 184 elective surgery patients of American Society of Anaesthesiologist (ASA) physical status I and II. Anesthesia was induced with propofol. Patients were randomly allocated into two groups with 92 patients in each. All the patients received Ringer’s Lactate (10 ml/kg) and premedicated with fentanyl (2 mcg/kg) and midazolam (0,05 mg/kg) before induction of anesthesia. Group A was performed passive leg raising 45 degree 1 minute before injection of propofol until the end of study and group B (control) did not receive any maneuver. The measurements of heart rate , arterial blood pressure and oxygen saturation was obtained before propofol injection, 1 minute and 3 minutes after propofol injection. Hypotension was defined as drop in systolic arterial pressure more than or equal 20 % of baseline. parametric data were analyzed with t-test and categorical data was done by using Chi-square test. A p value of less than 0,05 was consider significant. Results : Demografic characteristics (age, sex, body weight and height) and baseline haemodynamic parameters of the patients were similar in two groups (p > 0.05) except for BMI (p < 0.05) . The incidence of hypotension was significantly lower in group A (12 %, ) than group B (27,2%) at the first minute after propofol injection, p value = 0.016 (p < 0,05). In the third minute, incidence of hypotension was also significantly lower in group A (15,2%) than group B (23,9%), p value = 0,014 (p < 0,05). Conclusion : Leg elevation maneuver 45º significantly decrease incidence of hypotension after propofol induction.